2016
DOI: 10.1016/j.bjm.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the protective, curative, and eradicative applications of chitosan against Penicillium expansum in apples

Abstract: Apple is one of the most important temperate fruit to Brazil economy, and the use of synthetic chemicals has been the main method for reducing postharvest diseases, such as the blue mold, caused by Penicillium expansum. This work intends to evaluate the practical utilization of chitosan for blue mold control. For this purpose, fruits were treated in a preventive and curative way, immersing the fruits in chitosan solution (5 or 10 mg mL−1), or adding a single drop of this solution (10 mg mL−1) directly into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…A major advantage of using the numerical weather prediction data is that disease forecast information should be available prior to actual infection by pathogen (Firanj Sremac et al, 2018), which allows crop growers to take better options of disease control measures including both protective and curative chemicals (Beresford and Manktelow, 1994). By incorporating protective measures in plant disease management, it is possible to suppress development of fungicide resistance in pathogen population (Darolt et al, 2016;Hollomon, 2015;Horsfield et al, 2010). Besides, the UM-predicted weather data are available free of charge (Magarey and Isard, 2017) throughout the whole country of Korea at the spatial resolution of 1.5 km × 1.5 km.…”
Section: Discussionmentioning
confidence: 99%
“…A major advantage of using the numerical weather prediction data is that disease forecast information should be available prior to actual infection by pathogen (Firanj Sremac et al, 2018), which allows crop growers to take better options of disease control measures including both protective and curative chemicals (Beresford and Manktelow, 1994). By incorporating protective measures in plant disease management, it is possible to suppress development of fungicide resistance in pathogen population (Darolt et al, 2016;Hollomon, 2015;Horsfield et al, 2010). Besides, the UM-predicted weather data are available free of charge (Magarey and Isard, 2017) throughout the whole country of Korea at the spatial resolution of 1.5 km × 1.5 km.…”
Section: Discussionmentioning
confidence: 99%
“…Postharvest diseases of apple are caused by a range of fungal pathogens (Sutton 2014). The most common and destructive postharvest disease of stored apples is the blue mold caused by Penicillium expansum (da Rocha et al 2016;Darolt et al 2016;Spadaro 2010;Spotts et al 1999;Yu et al 2014). Several other species such as P. chrysogenum (Rharmitt et al 2016), P. solitum (Sholberg et al 2005), P. crustosum , Penicillium carneum (Peter et al 2012), Penicillium griseofulvum (Spadaro et al 2011) and Penicillium biourgeianum (Azam et al 2016) have also been reported to be responsible for the rot.…”
Section: Introductionmentioning
confidence: 99%
“…sulfato de cobre tribásico), es el principal método de control de este tipo de fitopatógenos; no obstante, el uso de estos compuestos, además de incrementar los costos de producción y evitar la exportación de la fresa, pueden ocasionar aislados resistentes al ingrediente activo (Weber, 2011), además del riesgo en la salud humana que conlleva la persistencia de residuos químicos en los frutos (Botelho et al, 2010). Asimismo, y debido al interés que han mostrado los consumidores, quienes exigen alimentos libres de plaguicidas químicos en los alimentos, es necesario realizar la búsqueda de nuevas alternativas para el control de este tipo de patógenos (Darolt et al, 2016).…”
Section: Introductionunclassified
“…Los frutos se colocaron en cajas de plástico estériles con algodón estéril húmedo y se incubaron a 2 ± 2.0 °C por 7 días. Transcurrido este tiempo, los frutos se almacenaron a temperatura ambiente (25 ± 2.0 °C) durante 3 días para simular las condiciones de almacenamiento de la fresa para exportación(Romanazzi et al, 2013;Darolt et al, 2016). Se realizó el mismo procedimiento para los controles negativos: ácido acético al 1 % para el quitosano y el compósito quitosano/octanoato de sodio; etanol absoluto para el ácido decanoico y ácido acético al 1 % y etanol absoluto para el compósito quitosano/ácido decanoico.…”
unclassified